Utilização do Algoritmo Sebal para o cálculo das componentes do balanço de energia em uma região de savana em Santarém, Pará, Brasil - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
The Amazonian diversity results from a balanced relationship between biotic and abiotic factors, so any change in the climate can cause changes in the lives of populationsThe Amazon is characterized by the presence of the tropical forest, but there are areas with characteristics similar to the cerrados. Driven by man's action, these areas would be expanding, leading the place to a process of savanna that could result in climate change. In this context, the present work seeks to characterize the components of the radiation and energy balances in Savanna areas in the Amazon. The study site will be an Amazonian Savannah area, in Santarém, Pará, using multispectral image data from the MODIS sensor, on board the TERRA satellite, obtained free of charge on the LPDAAC / USGS website (https://lpdaac.usgs.gov/ ). After image processing, the Surface Energy Balance Algorithm for Land (SEBAL) algorithm will be applied, which, through computational routines, provides the components of radiation and energy balance. The present study confirmed results of greater short wave reflection (Albedo) and greater propagation of long wave radiation from surface to atmosphere, thus higher heat emissions to the atmosphere and reduction in radiation balance in the Savannah area in relation to the forest. There was a reduction in the latent heat flow (LE) and an increase in the sensitive heat flow (H) and soil (G) in relation to the forest. The energy balance showed a greater percent of energy being used for LE, about 55,6 %, justified by the good availability of water in the open environment, followed by H with 31,5 % and G with 12,9 %, the latter confirms its importance for a better closing of the energy balance.
Keywords: Balanço de energia; MODIS; SEBAL; Savana amazônicas; Alter do Chão; CNPQ::CIÊNCIAS BIOLÓGICAS; Processos de Interação da Biosfera e Atmosfera.